An Update on Targeted Treatment of IgA Nephropathy: An Autoimmune Perspective - Huang, Xin; Xu, Gaosi (Frontiers in Pharmacology, 2021)
Immunoglobulin (Ig) A nephropathy (IgAN) is the commonest form of primary glomerulonephritis worldwide and is, considered a significant cause of end-stage renal disease in young adults. The precise pathogenesis of IgAN is unclear. The clinical and pathological features vary significantly between individuals and races, which makes treating IgAN difficult. Currently, the therapeutic strategies in IgAN are still optimal blood pressure control and proteinuria remission to improve the renal function in most cases. Immunosuppressive drugs such as corticosteroids can be considered in patients with persistent proteinuria and a high risk of renal function decline; however, they include a high toxicity profile. Therefore, the safety and selectivity of medications are critical concerns in the treatment of IgAN. Various pharmacological therapeutic targets have emerged based on the evolving understanding of the autoimmune pathogenesis of IgAN, which involves the immune response, mucosal immunity, renal inflammation, complement activation, and autophagy; treatments based on these mechanisms have been explored in preclinical and clinical studies. This review summarizes the progress concerning targeted therapeutic strategies and the relevant autoimmune pathogenesis in IgAN.